2019
DOI: 10.1002/mame.201800688
|View full text |Cite
|
Sign up to set email alerts
|

Graphene‐Based Bimorph Actuators with Dual‐Response and Large‐Deformation by a Simple Method

Abstract: There is a high demand for the design of high‐performance soft actuators with multi‐stimuli response and easy fabrication. Here, soft bimorph actuators consisting of graphene and polypropylene are fabricated by the drop‐coating of graphene film and subsequent adhesion of polypropylene on the graphene film. The fabrication method is simple, fast, and scalable, and this bimorph actuator exhibits optically and electrically induced actuation with large and reversible deformation (angle change > 100°), fast respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…To act as a plant, the actuating properties responding to triggers are necessary. Based on the light‐driven bending performance, the carbon‐based actuators can be applied in the plantoid design as the organ for artificial plants, [ 6,69,96,124 ] such as the petal for artificial flowers. Inspired by the blooming process of flowers, the light‐driven shape‐changing flower was fabricated by using six MWCNT–polylactic acid/paper bilayer petals ( Figure a).…”
Section: Applications Of Carbon‐based Soft Actuatorsmentioning
confidence: 99%
“…To act as a plant, the actuating properties responding to triggers are necessary. Based on the light‐driven bending performance, the carbon‐based actuators can be applied in the plantoid design as the organ for artificial plants, [ 6,69,96,124 ] such as the petal for artificial flowers. Inspired by the blooming process of flowers, the light‐driven shape‐changing flower was fabricated by using six MWCNT–polylactic acid/paper bilayer petals ( Figure a).…”
Section: Applications Of Carbon‐based Soft Actuatorsmentioning
confidence: 99%
“…If ordinary glue is used, the Joule heat generated when the voltage is applied will cause the glue to melt, resulting in the separation of the two layers of graphite and PE film, and therefore in damage to the device. The PE film was chosen because it has a large thermal expansion coefficient 20 × 10 To verify its driving performance, we trimmed the device into the U-shaped structure commonly used in an electrothermal actuator, [19] which forms a loop by connecting the electrodes at the two U-shaped ports for easy operation. When the voltage was turned off, heat dissipated into the surrounding air and the actuator returned to its original state, indicating the reversibility of the PE/graphite actuator.…”
Section: Structure Of Actuator Analysismentioning
confidence: 99%
“…At the same time, it also proved the stability of the intermediate adhesive in terms of bonding the two layers of film. SACNS/PDMS 30×6×0.77 mm 100 40 [9] RGO/PDMS 8×2×0.12 mm 35 80 12 [3] Graphite/PI 270 216 12.5 [18] RGO/ PE 50 60 [19] GO/RGO 120 80 7 [14] CFF/EVA 60×5×0.35 100 10 [8] Graphite/PI 40×5×0.14 mm 248.6 300 6 [12] PI/Paper/PDA-Zn2+/(M/G) 40×15 mm 120 10 [13] PDMS/carbon tape 160 20(W) [15] PTFE/MXene/PI 30×5 mm 120 100 6…”
Section: Performance According To Actuator Analysismentioning
confidence: 99%
“…A very recent and interesting study was reported by Wang group (Chang et al, 2019). The soft actuator with the construction of asymmetric based on graphene/polypropylene was fabricated by adhesion the polypropylene film on one side of the drop-coating graphene film.…”
Section: Electrically Stimulated Actuationmentioning
confidence: 99%